Budidaya Ikan Air Tawar di Lingkungan Pesantren - Akshari Tahir Lopa; Anas Arfandi (DEDIKASI, 2020)
This activity aims to 1) utilize rainwater catchment areas in Pesantren Somba Opu District, Gowa Regency as freshwater fish ponds; 2) create a freshwater fish breeding pond, 3) build a fishing house, and 4) provide marketing management training for freshwater fish. The specific target to be achieved is the Nur Fadhilah pesantren to be independent and have a regular income from the freshwater fish business by utilizing rainwater catchment areas as freshwater fish ponds. The method implemented in this activity is education and training through counseling, accompanied by practices and demonstrations which include the introduction of intensive aquaculture, introduction of local feed ingredients and preparation, as well as the production and production of freshwater fish species that allow them to be maintained in this area. Counseling is an educational system outside of school, where adults and youth learn while working. The results of the activity show that 2 ar plots of freshwater fish ponds were made to maintain 10,000 fish. Maintenance of fish for 3 months produces an average of 4-5 fish per kilo. From the evaluation of the activities it was concluded that the respondents' understanding of freshwater aquaculture was very good up to 86.67%. However, understanding of making brochures, promotional materials as well as the ability of product marketing and preparation of business plans is not optimal. The entrepreneurial spirit of the respondents was very good, even though only 73.33% of the respondents achieved it. Overall, respondents gave positive opinions on the benefits of activities which reached 93.33% with Very Good responses.